Early postnatal growth failure in infants <1500 g in a Ugandan referral hospital: a retrospective cohort study - Noela Regina Akwi Okalany; Ingunn Marie S. Engebretsen; Francis Okello; Peter Olupot-Olupot; Kathy Burgoine (BMC, 2024)
Abstract Background Postnatal growth failure (PGF), a multifactorial condition is common in preterm infants and infants born weighing <1500 g and is associated with impaired neurodevelopmental and growth outcomes. In low-resource settings, like Uganda, parenteral nutrition and breastmilk fortifier are often unavailable, and preterm infants rely solely on their mother's expressed breastmilk, which can be inadequate. This retrospective cohort study, conducted in a level II neonatal unit in eastern Uganda, aimed to evaluate the incidence of and risk factors for postnatal growth failure among infants <1500 g. Methods The study included infants with birthweight <1500 g, admitted within 24 h of birth, and who spent 7 or more days in the neonatal unit. Major congenital malformations or a diagnosis of hypoxic ischemic encephalopathy were exclusion criteria. PGF was defined as a decrease in weight Z score between birth and discharge of more than − 1.28. Data on feeding, anthropometry, co-morbidities, and clinical measures were extracted from medical records. Statistical analyses were performed using Stata 17.0 with crude and adjusted relative risks (RR) were reported. Results One hundred and four infants were recruited, including 47 (45.2%) male and 57 (54.8%) female, with a mean birth weight of 1182 g (SD 18 g, 95% CI: 1140, 1210). Almost half were small for gestational age, most were singletons (66.3%), and most were born by spontaneous vaginal delivery (82.7%). PGF was observed at discharge in 75.9% (N = 79). Clinical risk factors for PGF included: small for gestational age (cRR 1.25, 95% CI: 1.01, 1.53), respiratory distress syndrome (aRR 1.30 95% CI: 1.01, 1.67), duration of bubble continuous positive airway pressure use (aRR 1.35, 95% CI: 1.10, 1.66), sepsis requiring second line (aRR 1.58, 95% CI: 1.22, 2.04) and third line treatment (aRR 1.46, 95% CI: 1.20, 1.77), prolonged time to achieve full feeds (aRR 1.30, 95% CI: 1.01, 1.66) and prolonged hospitalisation (aRR 1.85, 95% CI: 1.31, 2.61). Conclusion PGF was common among infants <1500 g in this hospitalised cohort who were primarily fed on their mother's own milk. Urgent action is needed to enhance postnatal growth in this vulnerable patient group. Future research should focus on exploring multidisciplinary interventions that can improve growth outcomes in this population and understanding the long-term implications and need for care for these infants.